Data describing the swelling behavior and cytocompatibility of biodegradable polyelectrolyte hydrogels incorporating poly(L-lysine) for applications in cartilage tissue engineering - Lam, Johnny (Data Brief, 2016)
This data article presents data associated with the research article entitled “Evaluation of cell-laden polyelectrolyte hydrogels incorporating poly(L-lysine) for applications in cartilage tissue engineering” (Lam et al., 2016) [1]. Synthetic hydrogel composites fabricated using oligo(poly(ethylene glycol) fumarate) (OPF) macromers were utilized as vehicles for the incorporation of poly(L-lysine) (PLL) as well as the encapsulation of mesenchymal stem cells (MSCs). PLL-laden and PLL-free hydrogels were fabricated to characterize the main and interaction effects of OPF molecular weight, PLL molecular weight, and PLL loading density on the swelling and degradation of synthetic OPF hydrogels. Cells were then encapsulated within such hydrogels for in vitro culture and examined for viability, biochemical activity, and chondrogenic gene expression. These data, which are supplementary to the associated research article (Lam et al., 2016) [1], are presented here.